Analysis and Interpretation of the Human Microbiome. Issue 7 (July 2016) - Ashton, James J.; Beattie, R. Mark; Ennis, Sarah; Cleary, David W.
Abstract : Abstract: Microbiome research has experienced an unprecedented level of growth over the last decade. This is largely due to revolutionary developments in, and accessibility to, DNA sequencing technologies that have enabled laboratories with even modest budgets to undertake projects. Study of the human microbiome in particular has seen a surge in interest, and although a lot of time and money has been focused on health and disease, the clinical interpretation of these data and the ability of clinicians to understand these studies in the context of disease are less straightforward. Conditions such as inflammatory bowel disease, asthma, and cancer have seen a huge increase in research focused on the role of microbiome in disease pathogenesis, but the ability of clinicians to appraise and use these data is largely lacking. The purpose of this article is to provide an introduction for clinicians and nonclinicians wishing to learn about and engage in microbiome research. It details the background of microbiome research and discusses the process of generating 16S rRNA sequencing data, the most commonly used method for microbiome analysis. We discuss the interpretation of results in a clinical context, commonly used metrics for analysis and discuss future impact and direction for microbiome research. The meteoric rise of genomic medicine to the brink of routine clinical use should be seen as a blueprint for the microbiome; the ability for physicians to understand and interpret these data is vital to this growth and aiding clinicians (and researchers) to participate in further microbiome research. Abstract : Article first published online 31 May 2016.